International capital movement under the low of the International monetary fund - Gold, Joseph (Washington, 1977)
The Articles of Agreement of the International Monetary Fund are the central legal instrument of the international monetary system. The fundamental principles of international law with respect to the movement of capital, but by ans the whole of the law on the subject, are to be found in that instrument. The primary principle of the Articles with respect to capital is that member countries of the Fund, which will usually be referred to as "members" in this pamphlet, are free to control international movements of capital. This principle retained its pristine formulation in the first amendment of the Articles. The principle will be unchanged in the second amendment even though in connection with reform of the international monetary system the question was raised whether the Fund should have some authority to approve or disapprove controls of capital transfers. It will be seen that there was a certain amount of support for authority of this kind before the original Articles were drafted. Radical changes will be made by the second amendment in the obligations of members with respect to exchange arrangements. The new provisions might have effects on capital controls in the future, but it is not possible at this time to predict these effects.
Keywords: International finance